Editorial [Hot topic: Proteomics Approaches to Plant Microbe Interactions (Guest Editor: Francisco Javier Fernandez-Acero)] - Javier Fernandez-Acero, Francisco (Current Proteomics, 2010)
Since the early days of the human history, the development of agriculture has been crucial for the first human settlements and its transformation in our first cities. Nowadays, agriculture is still one of the main human activities. The development of molecular tools has increased the amount of relevant biological information directed to improve crops maintenance in several ways, such as plant development or its resistance to plant diseases. Between these molecular techniques, proteomics tools and technologies have become a great relevance during the last years. Some authors have labeled the present times as the “postgenomic era”. Proteomics approaches had revealed its utility and relevance in many studies, showing that the exclusive use of genomic approaches contributes to losses of significant information, as the proteins and not the genes coding them, are finaly responsible for the observed phenotype. In this context, we had prepared a compendium of the different aspects related to the proteomics approaches to study the interaction of plant and microbes. In this special issue, we had covered the relevance of these interactions in several ways by describing from a proteomics point of view, the relevance between roots and soil microbes, and the last advances related to virus and bacterial interactions with plants. Plant pathology has been tackled by studying the last advances in the proteomics of plant pathogenic fungi, the use of proteomics to describe bio-control agents, as well as, the development of new ways to study this relationship by using activity based proteomics probes, which had opened new frontiers beyond standard proteomics tools. The plant point of view has been included in a specific plant biotic stress contribution. Technical contributions are indispensable due to most of the used biological systems presenting poor molecular information. For this reason, the protein identification by MS/MS and the development of new gel-free approaches has been included in our special issue. We Sincerely thank the issue contributors, as they had prepared a nice compendium which will be necessary for future researchers in this field. Many of its future challenges that may likely be encountered have been described here. By summarizing, the main problem is to transfer our lab experiments to the crops field. In spite of several relevant advances, we have not yet developed any fungicide based on molecular information. We still use the chemical compounds that present several environmental problems and health risk to the farmers and consumers. The development of plants resistant to pathogen attack, new bio control agents and plant development improvement will be the areas of future proteomics research.